Fluorinated waste and firefighting activities: biodegradation of hydrocarbons from petrochemical refinery soil co-contaminated with halogenated foams - Montagnolli, Renato Nallin [UNESP]; Lopes, Paulo Renato Matos [UNESP]; Bidoia, Ederio Dino [UNESP] (Springer Nature, 2018)
Perfluorinated compounds, including fluorotelomers, are important constituents of firefighting foams to extinguish fuel fires in the petrochemical industry, airports, and at fire-training sites. In this study, we monitored the biodegradation process in a co-contamination scenario with monoaromatic hydrocarbons commonly found in fuels (benzene, toluene) and fluorotelomers. The CO2 production rates were evaluated by a factorial design taking into account the effect of seasonality at in situ natural attenuation processes. Headspace analysis by gas chromatography with a thermal conductivity detector (GC-TCD) was applied to detect CO2 production, whereas monoaromatics were analyzed by gas chromatography coupled to mass spectrometry (GC–MS). According to our results, seasonality had a detectable effect during summer, yielding different CO2 production rates. Higher temperatures increased CO2 production rate, while higher concentrations of fluorotelomer inhibited the biodegradation process. On average, benzene and toluene were depleted 17.5 days earlier in control assays without fluorotelomers. Toluene removal efficiency was also notably higher than benzene. The noticeable decrease in degradation rates of monoaromatics was caused by perfluorinated compounds that are possibly linked to metabolic inhibition mechanisms. Fluorotelomer diminished catabolism in all of our batch cultures. In addition to this, an alternative production of by-products could be detected. Thus, we propose that transient components of the benzene and toluene degradation may be differentially formed, causing the benzene, toluene, and perfluorinated co-contaminations to go through switched metabolic stages under the presence of fluoride in a contamination scenario.
Keywords: Benzene; Bioremediation; Chromatography; Fluorotelomer; Halogenated waste; Perfluorinated compounds; Toluene